The Spiritual-Philosophical Interpretation Of Social Security And The Youth Phenomenon - Tukhtamurod Otamurodovich Mamatov (Zien Journals, 2025)
This article scientifically analyzes the impact of various social security issues and threats on the spiritual world of youth in the context of globalization, the scope, significance, and spheres of influence of information and globalization on these processes. At the same time, special attention is paid to certain problems arising in the field of youth education, their alignment with society in terms of social security, and their philosophical interpretation
Keywords: social security of youth; spiritual-philosophical interpretation; phenomenon